A tin-zinc-copper alloy and its preparation method and application
By controlling the composition range of elements such as tin, zinc, phosphorus, nickel and other elements and the content of copper, a tin-zinc copper alloy with high conductivity was prepared, which solved the problem of low conductivity of traditional materials and improved the conductivity and production efficiency.
Patent Information
- Application Number
- CN202211672984.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-12-26
AI Technical Summary
The traditional tin-phosphorus nickel-copper-based multi-component complex alloy materials have low conductivity, resulting in poor conductivity of electrical switch and socket components.
By controlling the composition range of elements such as tin, zinc, phosphorus, nickel, etc., and strictly controlling the copper content greater than 93.5 wt%, and the impurity content less than 0.2 wt%, a tin-zinc-copper alloy with high conductivity was prepared.
The conductivity of tin-zinc-copper alloy is improved to more than 30%, enhancing the conductive properties of the material, while reducing temperature rise, saving energy, and improving production efficiency.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of copper-based multi-component complex materials, and in particular to a tin-zinc-copper alloy and a preparation method and application thereof. Background Art
[0002] Tin-phosphorus-nickel-copper based alloy has excellent qualities such as high strength, high elasticity, good wear resistance and good corrosion resistance. Its strips and other products and parts have good electrical and thermal conductivity as well as good elasticity and fatigue resistance. Its application range is very wide, covering many fields such as modern science and technology aerospace, aviation, navigation, electronics, telecommunications, atomic energy, instrumentation, construction, and civil use. With the progress of human society, the development of these fields has an increasing demand for such materials.
[0003] The conductivity IACS of the traditional Sn-P-N-Cu-based multi-component complex alloy material is only 16%, and the electrical switch and socket components made from it have the problem of low conductivity. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a tin-zinc-copper alloy and a preparation method and application thereof. The tin-zinc-copper alloy provided by the present invention has high electrical conductivity.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a tin-zinc-copper alloy, which comprises the following elements in percentage by mass: 1.5-2.0% tin, 0<phosphorus<0.15%, 0<nickel<1.2%, 3.5-5.0% zinc, and the remainder copper and inevitable impurities.
[0007] Preferably, the impurities include one or more of Pb, Fe, Bi, Al, Si, Sb, S, As, Cr, Cd, Mg and Mn.
[0008] Preferably, the mass percentage of impurities in the tin-zinc-copper alloy is less than 0.2%.
[0009] Preferably, the tensile strength of the tin-zinc-copper alloy is 490-520 N / mm 2 , elongation is 10-20%, Vickers hardness is 150-175, and conductivity IACS>30%.
[0010] Preferably, the mass percentage of tin in the tin-zinc-copper alloy is 1.623%, the mass percentage of phosphorus is 0.12%, the mass percentage of nickel is 0.226%, the mass percentage of lead is 0.0076%, the mass percentage of iron is 0.0428%, the mass percentage of zinc is 4.1%, the mass percentage of bismuth is 0.0015%, the mass percentage of silicon is 0.0035%, the mass percentage of antimony is 0.0037%, the mass percentage of arsenic is 0.002%, the mass percentage of magnesium is 0.00014%, and the mass percentage of copper is 93.8%.
[0011] The present invention also provides a method for preparing the tin-zinc-copper alloy described in the above technical solution, comprising the following steps:
[0012] The tin-zinc-copper alloy is obtained by sequentially carrying out batching, smelting, horizontal continuous casting, milling, rough rolling, intermediate annealing, trimming, pre-finish rolling, re-annealing, pickling, finish rolling, degreasing, straightening and shearing according to the element composition.
[0013] Preferably, the intermediate annealing is performed at a temperature of 598-603° C. for 5 hours.
[0014] Preferably, the re-annealing temperature is 458-463° C. and the time is 4.5 h.
[0015] Preferably, the total processing rate of the pre-finish rolling is 63%, and the number of rolling passes is 3 times.
[0016] The present invention also provides the use of the tin-zinc-copper alloy described in the above technical solution or the tin-zinc-copper alloy prepared by the preparation method described in the above technical solution in the preparation of electrical products.
[0017] The invention provides a tin-zinc-copper alloy, which comprises the following elements in percentage by mass: 1.5-2.0% tin, 0<phosphorus<0.15%, 0<nickel<1.2%, 3.5-5.0% zinc, and the remainder copper and inevitable impurities.
[0018] The present invention controls the range of elemental components, strictly controls the content of tin, zinc, phosphorus, and nickel elements, and mechanical energy, ensures that the copper content is greater than 93.5wt%, and controls other impurity components below 0.2wt%, effectively ensuring that the product conductivity IACS is above 30%, and improving the conductivity. In addition, the temperature rise of the tin-zinc-copper alloy of the present invention is low, which can reduce energy consumption and achieve the purpose of energy saving and efficiency improvement.
[0019] The present invention also provides a method for preparing the tin-zinc-copper alloy described in the above technical solution. The processing technology of the present invention is reduced to two annealing steps, and the preparation method has a short production cycle, which is shortened by 1 to 2 days, thereby reducing costs and improving efficiency. DETAILED DESCRIPTION
[0020] The invention provides a tin-zinc-copper alloy, which comprises the following elements in percentage by mass: 1.5-2.0% tin, 0<phosphorus<0.15%, 0<nickel<1.2%, 3.5-5.0% zinc, and the remainder copper and inevitable impurities.
[0021] The mass percentage of the tin element in the tin-zinc-copper alloy provided by the present invention is preferably 1.6-1.8%. In the present invention, the role of the tin element is to improve the elasticity of the alloy and increase the ductility of the alloy.
[0022] The mass percentage of phosphorus in the tin-zinc-copper alloy provided by the present invention is preferably 0.01-0.13%. In the present invention, the phosphorus element has the function of deoxidation, increasing the fluidity of the alloy liquid during the casting process, and improving the casting structure.
[0023] The mass percentage of nickel in the tin-zinc-copper alloy provided by the present invention is preferably 0.1-0.5%. In the present invention, the role of the nickel element is to improve the mechanical properties of the alloy material and meet the physical property requirements.
[0024] The mass percentage of the tin element in the tin-zinc-copper alloy provided by the present invention is preferably 4 to 4.5%. In the present invention, the role of the zinc element is to reduce the reverse segregation defect of tin and improve the casting structure.
[0025] The mass percentage of copper element in the tin-zinc-copper alloy provided by the present invention is preferably greater than 93.5%.
[0026] In the present invention, the impurities preferably include one or more of Pb, Fe, Bi, Al, Si, Sb, S, As, Cr, Cd, Mg and Mn.
[0027] In the present invention, the mass percentage of impurities in the tin-zinc-copper alloy is preferably less than 0.2%.
[0028] In the present invention, the tensile strength of the tin-zinc-copper alloy is preferably 490 to 520 N / mm 2 The elongation is preferably 10-20%, the Vickers hardness is preferably 150-175, and the electrical conductivity IACS is preferably >30%.
[0029] In the present invention, the mass percentage of tin in the tin-zinc-copper alloy is preferably 1.623%, the mass percentage of phosphorus is preferably 0.12%, the mass percentage of nickel is preferably 0.226%, the mass percentage of lead is preferably 0.0076%, the mass percentage of iron is preferably 0.0428%, the mass percentage of zinc is preferably 4.1%, the mass percentage of bismuth is preferably 0.0015%, the mass percentage of silicon is preferably 0.0035%, the mass percentage of antimony is preferably 0.0037%, the mass percentage of arsenic is preferably 0.002%, the mass percentage of magnesium is preferably 0.00014%, and the mass percentage of copper is preferably 93.8%.
[0030] The present invention also provides a method for preparing the tin-zinc-copper alloy described in the above technical solution, comprising the following steps:
[0031] The tin-zinc-copper alloy is obtained by sequentially carrying out batching, smelting, horizontal continuous casting, milling, rough rolling, intermediate annealing, trimming, pre-finish rolling, re-annealing, pickling, finish rolling, degreasing, straightening and shearing according to the element composition.
[0032] In the present invention, the total processing rate of the rough rolling is preferably 86%, and preferably includes the following steps: the incoming material with a thickness of 14.6 mm is rolled to 2.0 mm through 6 rolling passes, and is coiled on a small reel, requiring the surface to be free of scratches, cracks, and peeling.
[0033] In the present invention, the intermediate annealing temperature is preferably 598-603° C., more preferably 599-600° C., and the time is preferably 5 hours.
[0034] In the present invention, the re-annealing temperature is preferably 458-463° C., more preferably 460° C., and the time is preferably 4.5 h.
[0035] In the present invention, the total processing rate of the pre-finishing rolling is preferably 63%, and preferably includes the following steps: the incoming material with a thickness of 2.0 mm is kept at 600°C for 5 hours, cooled to below 90°C and taken out of the furnace, and rolled three times to make the thickness reach the bottom size. The product surface is required to be free of scratches, cracks, peeling and other defects, and the plate shape must be flat.
[0036] The present invention also provides the use of the tin-zinc-copper alloy described in the above technical solution or the tin-zinc-copper alloy prepared by the preparation method described in the above technical solution in the preparation of electrical products.
[0037] The present invention has no particular limitation on the specific manner of the application, and any manner familiar to those skilled in the art may be used.
[0038] In order to further illustrate the present invention, the tin-zinc-copper alloy provided by the present invention and its preparation method and application are described in detail below in conjunction with examples, but they should not be construed as limiting the protection scope of the present invention.
[0039] Example 1
[0040] A tin-zinc-copper alloy, product grade HSn92-1, specification 0.60×400mm, state Y2, element percentage composition: copper 93.8%, tin 1.623%, phosphorus 0.127%, nickel 0.226%, zinc 4.1%, other trace element impurity content 0.12%, of which the content of lead is 0.0076%, the content of iron is 0.0428%, the content of bismuth is 0.0015%, the content of silicon is 0.0035%, the content of antimony is 0.0037%, the content of arsenic is 0.002%, and the content of magnesium is 0.00014%. The actual measured data of the physical and chemical properties of the product are as follows: tensile strength 508N / mm 2 , elongation 12%, micro Vickers hardness HV1=156, and electrical conductivity IACS is 30.8%.
[0041] The obtained tin-zinc-copper alloy is made into 118-type 15-hole F610ABL3, and the pre-life temperature rise test is carried out according to the test standard GB / T2099.1-2021. For multiple fixed sockets with shared wiring terminals, a 20A test current is passed. a) The first test plug is inserted into a socket and 70% of the test current (14A) is passed; b) The second test plug is inserted into another socket, and the balance of the total test current is passed to the plug at the same time (6A). The total nominal load temperature rise of the power supply cable terminal does not exceed 45K. The test results are: 6A for the middle two plugs, 14A for the third plug, and 6A for the fourth plug. 4A, 1#38.9K(L)43.5K(N), two plugs 14A, three plugs 6A, 1#38.4K(L)43.9K(N), the test result is qualified; diagonal two plugs 6A, three plugs 14A, 1#41.8K(L)42.8K(N), two plugs 14A, three plugs 6A, 1#33.5K(L)42.5(N), the test result is qualified; right two plugs 6A, three plugs 14A, 1#40.1K(L)39.1K(N), two plugs 14A, three plugs 6A, 1#41.8K(L)42.8K(N), the test result is qualified.
[0042] Preparation method:
[0043] According to the elemental composition, the materials are batched, smelted, horizontally continuously cast, milled, rough rolled, intermediate annealing, trimmed, pre-finished rolled, re-annealed, pickled, finished rolled, degreased, straightened and sheared in sequence to obtain tin-zinc-copper alloy. The processing rate of rough rolling is 86%. The material thickness is rolled from 14.6 to 2.0 mm through 6 passes and rolled on a small reel. The surface is required to be free of scratches, cracks and peeling. The intermediate annealing temperature is 599°C for 5 hours, and the re-annealing temperature is 460°C for 4.5 hours. The total processing rate of pre-finished rolling is 63%. The material thickness is 2.0 mm, and it is kept at 600°C for 5 hours, cooled to below 90°C and taken out of the furnace. After 3 passes of rolling, the thickness reaches the bottom size. The product surface is required to be free of scratches, cracks, peeling and other defects, and the plate shape must be flat.
[0044] Example 2
[0045] A tin-zinc-copper alloy, specification 0.60×400mm, state Y2, element percentage composition: copper 94.26%, tin 1.5%, phosphorus 0.14%, nickel 1.0%, zinc 3.0%, other trace element impurity content 0.1%, product physical and chemical properties measured data are as follows: tensile strength 503N / mm 2 , elongation 14%, micro Vickers hardness HV1=155, and electrical conductivity IACS is 31.9%.
[0046] The obtained tin-zinc-copper alloy is made into 118-type 15-hole F610ABL3, and the pre-life temperature rise test is carried out according to the test standard GB / T2099.1-2021. For multiple fixed sockets with common wiring terminals, a 20A test current is passed. a) The first test plug is inserted into a socket and 70% of the test current (14A) is passed; b) The second test plug is inserted into another socket, and the balance of the total test current is passed to the plug at the same time (6A). The total nominal load temperature rise of the power supply cable terminal does not exceed 45K. The test results are: 6A for the middle two plugs, Three plugs 14A, 1#38.9K(L)39.6K(N), two plugs 14A, three plugs 6A, 1#39.1K(L)40.2K(N), the test result is qualified; diagonal two plugs 6A, three plugs 14A, 1#38K(L)39.5K(N), two plugs 14A, three plugs 6A, 1#37.9K(L)38.6(N), the test result is qualified; right two plugs 6A, three plugs 14A, 1#39K(L)40.1K(N), two plugs 14A, three plugs 6A, 1#39.8K(L)41K(N), the test result is qualified.
[0047] Preparation method:
[0048] According to the element composition, batching, smelting, horizontal continuous casting, milling, rough rolling, intermediate annealing, trimming, pre-finishing rolling, re-annealing, pickling, finishing rolling, degreasing, straightening and shearing are carried out in sequence to obtain tin-zinc-copper alloy. The rough rolling processing rate is 86%. The incoming material thickness is 14.6 and rolled to 2.0mm through 6 passes. The small coil is rolled and the surface is required to be free of scratches, cracks and peeling. The temperature of the intermediate annealing is 603℃ for 5h, the temperature of the re-annealing is 461℃ for 4.5h, and the total processing rate of pre-finishing rolling is 63%. The incoming material thickness is 2.0mm, and it is kept at 600℃ for 5h, cooled to below 90℃ and taken out of the furnace. After 3 passes of rolling, the thickness reaches the bottom size. The product surface is required to be free of scratches, cracks, peeling and other defects, and the plate shape must be flat.
[0049] Example 3
[0050] A tin-zinc-copper alloy, specification 0.60×400mm, state Y2, element percentage composition: copper 94.55%, tin 1.8%, phosphorus 0.05%, nickel 0.05%, zinc 3.5%, other trace element impurity content 0.05%, product physical and chemical properties measured data are as follows: tensile strength 495N / mm 2 , elongation 16%, micro Vickers hardness HV1=153, and electrical conductivity IACS is 33.5%.
[0051] The obtained tin-zinc-copper alloy is made into 118-type 15-hole F610ABL3 for pre-life temperature rise detection. The detection standard is GB / T2099.1-2021. For multiple fixed sockets with shared wiring terminals, a 20A test current is passed. a) The first test plug is inserted into a socket and 70% of the test current (14A) is passed; b) The second test plug is inserted into another socket, and the balance of the total test current is passed to the plug at the same time (6A). The total nominal load temperature rise of the power supply cable terminal does not exceed 45K. The test results are: 6A for the middle two plugs and 6A for the three plugs 14A, 1#37K(L)38.3K(N), second plug 14A, third plug 6A, 1#38K(L)39.1K(N), the test result is qualified; diagonal second plug 6A, third plug 14A, 1#37.5K(L)38.6K(N), second plug 14A, third plug 6A, 1#36.5K(L)38.1K(N), the test result is qualified; right second plug 6A, third plug 14A, 1#36.9K(L)37.8K(N), second plug 14A, third plug 6A, 1#37.4K(L)38.1K(N), the test result is qualified.
[0052] Preparation method:
[0053] According to the element composition, batching, smelting, horizontal continuous casting, milling, rough rolling, intermediate annealing, trimming, pre-finishing rolling, re-annealing, pickling, finishing rolling, degreasing, straightening and shearing are carried out in sequence to obtain tin-zinc-copper alloy. The rough rolling processing rate is 86%. The incoming material thickness is 14.6 and rolled to 2.0mm through 6 passes. The small coil is rolled and the surface is required to be free of scratches, cracks and peeling. The temperature of intermediate annealing is 600℃ for 5h, the temperature of re-annealing is 460℃ for 4.5h, and the total processing rate of pre-finishing rolling is 63%. The incoming material thickness is 2.0mm, and it is kept at 600℃ for 5h, cooled to below 90℃ and taken out of the furnace. After 3 passes of rolling, the thickness reaches the bottom size. The product surface is required to be free of scratches, cracks, peeling and other defects, and the plate shape must be flat.
[0054] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A tin-zinc-copper alloy, characterized in that: Element mass percentage composition: copper 94.55%, tin 1.8%, phosphorus 0.05%, nickel 0.05%, zinc 3.5%, other trace element impurities 0.05%; The preparation method is as follows: According to the elemental composition, the materials are batched, smelted, horizontally continuously cast, milled, rough rolled, intermediate annealing, trimmed, pre-finished rolled, re-annealed, pickled, finished rolled, degreased, straightened and sheared in sequence to obtain tin-zinc-copper alloy. The processing rate of rough rolling is 86%. The material thickness is rolled from 14.6mm to 2.0mm through 6 passes and rolled on a small reel. The surface is required to be free of scratches, cracks and peeling. The intermediate annealing temperature is 600℃ for 5h, and the re-annealing temperature is 460℃ for 4.5h. The total processing rate of pre-finished rolling is 63%. The material thickness is 2.0mm, and it is kept at 600℃ for 5h, cooled to below 90℃ and taken out of the furnace. After 3 passes of rolling, the thickness reaches the bottom size. The product surface is required to be free of scratches, cracks and peeling defects, and the plate shape must be flat.
2. The method for preparing the tin-zinc-copper alloy according to claim 1, characterized in that: For the following steps: According to the elemental composition, the materials are batched, smelted, horizontally continuously cast, milled, rough rolled, intermediate annealing, trimmed, pre-finished rolled, re-annealed, pickled, finished rolled, degreased, straightened and sheared in sequence to obtain tin-zinc-copper alloy. The processing rate of rough rolling is 86%. The material thickness is rolled from 14.6mm to 2.0mm through 6 passes and rolled on a small reel. The surface is required to be free of scratches, cracks and peeling. The intermediate annealing temperature is 600℃ for 5h, and the re-annealing temperature is 460℃ for 4.5h. The total processing rate of pre-finished rolling is 63%. The material thickness is 2.0mm, and it is kept at 600℃ for 5h, cooled to below 90℃ and taken out of the furnace. After 3 passes of rolling, the thickness reaches the bottom size. The product surface is required to be free of scratches, cracks and peeling defects, and the plate shape must be flat.
3. Use of the tin-zinc-copper alloy according to claim 1 or the tin-zinc-copper alloy prepared by the preparation method according to claim 2 in the preparation of electrical products.
Citation Information
Patent Citations
Copper alloy sheet and production method for copper alloy sheet
CN103748244A
Precipitation-hardening copper alloy and application thereof
CN108285988A
Production method of copper-tin alloy strip
CN114525390A
New copper alloy for connections and junctions in general, industrial and even vehicle applications
DE19931803A1
Copper alloy for terminal and connector having superior migration resistance
JP1987199741A